(untitled) (Development Service Industry Management, 2025)
In line with the research topic, the theoretical and methodological framework of material incentives for employees of hotel enterprises in Ukraine has been thoroughly reviewed and systematized, with particular attention paid to the shortcomings of this approach. Material incentives in the hotel business, as in other industries, serve as a fundamental tool of human resource management, influencing employee performance, satisfaction, and retention. The purpose of this study is to analyze and identify the key shortcomings of material incentive systems used in Ukrainian hotel enterprises under the conditions of martial law. The object of the study is the deficiencies inherent in the current material incentive mechanisms applied within hotel enterprises. The subject of the study is the set of theoretical and methodological principles for identifying and understanding the limitations of material incentives for hotel employees in Ukraine. To date, most scholarly research has focused on demonstrating the positive outcomes of material motivation — such as increased productivity, engagement, and commitment. However, it is equally important to recognize that material incentives have significant drawbacks that may undermine long-term organizational effectiveness. This recognition is particularly relevant for hotel managers who must operate under the unique challenges imposed by wartime conditions. The complexity and volatility of the current environment emphasize the scientific relevance and novelty of this research. Undoubtedly, financial incentives remain one of the most effective and widely used forms of employee motivation. Yet, an overreliance on them can lead to several adverse consequences. The study identifies the main shortcomings of material incentives in the hotel industry: short-term effectiveness, decreased intrinsic motivation, the emergence of a consumer-oriented attitude toward work, heightened internal competition, inequity in performance evaluation, increased financial strain on the enterprise, neglect of collective results, and dependence on constant raises or bonuses. In times of martial law, when hotel businesses face uncertainty, limited resources, and emotional stress among employees, these issues become even more pronounced. Material incentives alone may fail to sustain motivation or foster a sense of unity and purpose. Therefore, it is essential to integrate material and non-material motivational factors into a comprehensive system. Non-material incentives—such as recognition, career development opportunities, involvement in decision-making, and a supportive corporate culture—can enhance employees’ intrinsic commitment and resilience, complementing financial rewards and ensuring the long-term sustainability of the enterprise. In conclusion, while material incentives play an important role in human resource management, they should not be perceived as a universal solution. A balanced approach that combines economic, psychological, and social aspects of motivation can help hotel enterprises maintain stability and productivity, even amid crisis conditions.